Effects of stent-assisted coiling in comparison with flow diversion on intracranial aneurysms - Guo, Hao; Liu, Jian-Feng; Li, Cong-Hui; Wang, Ji-Wei; Li, Hui; Gao, Bu-Lang (Frontiers in Neurology, 2022)
Objective: To investigate the efficacy and complications of stent-assisted coiling in comparison with flow diversion for wide-necked intracranial aneurysms. Methods: Patients wide-necked intracranial aneurysms treated with stent-assisted coiling or flow diversion were enrolled into stent-assisted coiling and flow diversion treatment group, respectively. The clinical and angiographic data were analyzed. Results: Sixty-one patients with intracranial aneurysms underwent stent-assisted coiling, including 35 (57.4%) female and 26 (42.6%) male patients with 21 (34.4%) ruptured and 40 (65.6%) unruptured aneurysms. Fifty-three patients underwent deployment of flow diverting devices, including 30 (56.6%) female and 23 (43.4%) male patients with 25 (47.2%) ruptured and 28 (52.8%) unruptured aneurysms. Stent-assisted coiling was performed successfully in 60 patients with 63 stents deployed, and immediate aneurysm occlusion was complete occlusion in 38 (62.3%), residual neck in 12 (19.7%), and residual aneurysm in ten (16.4%). Procedure-related complications included instent thrombosis in three (4.9%) patients, coil protrusion in three (4.9%), and rerupture of one (1.6%) aneurysm, with a total complication rate of 11.5%. In the flow diversion group, a Pipeline stent alone was deployed in each of 24 (45.3%) patients, stent plus adjunctive coiling in 29 (54.7%), and double stents in each of six (11.3%) patients. Immediately after treatment, complete occlusion was achieved in three (5.7%) patients with adjunctive coiling, residual neck in three (5.7%), and residual aneurysm in 47 (88.7%). Procedure-related complications included aneurysm rebleeding in one patient (1.9%). Clinical and angiographic follow-up was performed 13-49 months (median 29) after the procedure for 49 (80.3%) patients with stent-assisted coiling, with complete aneurysm occlusion in 27 (55.1%) aneurysms, residual neck in three (6.1%), residual aneurysm in five (10.2%), and recurrence in 14 (28.6%). Follow-up was performed 14-37 (median 25) months in 45 (84.9%) patients with flow diversion treatment, with complete occlusion in 39 (86.7%) patients, residual neck in five (11.1%), residual aneurysm in one (2.2%), and no aneurysm recurrence. Conclusions: Stent-assisted coiling and flow diversion are both safe and effective for the treatment of wide-necked intracranial aneurysms, however, flow diversion seems more efficient with more complete occlusion but few recurrence of aneurysms in the long run.